Health‐related quality of life in patients with haemophilia and inhibitors on prophylaxis with anti‐inhibitor complex concentrate: results from the Pro‐FEIBA study. (4th June 2013) - Gringeri, A.; Leissinger, C.; Cortesi, P. A.; Jo, H.; Fusco, F.; Riva, S.; Antmen, B.; Berntorp, E.; Biasoli, C.; Carpenter, S.; Kavakli, K.; Morfini, M.; et al.
Summary: Patients with haemophilia A and inhibitors are at high risk for severe bleeding, progression of joint disease and deterioration of health‐related quality of life (HRQoL). To determine the impact of prophylaxis with an activated prothrombin complex concentrate (aPCC) on HRQoL, HRQoL was assessed using the Short‐Form (SF)‐36 Health Survey and the EQ‐5D questionnaire in subjects ≥14 years participating in a prospective, randomized, crossover study comparing 6 months of aPCC prophylaxis with 6 months of on‐demand therapy. Eighteen of 19 patients completed the survey or questionnaire before and after the on‐demand therapy and prophylaxis periods. A general trend towards improved HRQoL after prophylaxis was observed for the 18 evaluable patients in all SF‐36 dimensions except for vitality/energy and physical functioning . After prophylaxis, 'good responders, ' defined as patients experiencing ≥50% reduction in bleeding, exhibited statistically and clinically significant differences in the physical component score ( P = 0.021), role – physical ( P = 0.042), bodily pain ( P = 0.015), and social functioning ( P = 0.036). Similarly, the EQ‐5D health profile showed a trend towards improvement after prophylaxis in all evaluable patients. Among the good responders, improvements did not differ from those observed after on‐demand treatment. EQ visual analogue scale values were slightly improved following prophylaxis for all evaluable patients and the EQ‐5D utility index improved in the good responders only. During prophylaxis, patients missed significantly fewer days from school or work because of bleeding than during on‐demand treatment ( P = 0.01). In conclusion, by significantly reducing bleeding frequency in good responders, aPCC prophylaxis improved HRQoL compared with on‐demand treatment.